IMPLEMENTASI METODE PRAKTIKUM MATERI CAMPURAN PADA SISWA KELAS VII SMP SANTO FRANSISKUS ASISI PONTIANAK - Goreti, Claudiana; Enawaty, Eny; Lestari, Ira (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aims to determine the differences in learning outcomes between students’ are given learning by practicum method and conventional methods, the magnitude effect of practicum method toward learning outcome and to describe students’ motivation of 7th grade SMP Santo Fransiskus Asisi Pontianak are given learning by practicum method in the chemical mixture material. The research method was quasi-experimental with nonequivalent control group design. The study sample was determined by Random sampling technique. The instrument that used were as a test of learning outcome in the form of essays and students’ motivation questionnaire. Based on data analysis using the U Mann-Whitney test, obtained value Asymp. sig. ((2-tailed) .006 indicating that there was a difference in students’ learning outcomes. The practicum method gave the effect of 21.90% on improving students’ learning outcomes. Motivation of students on learning practicum method in the chemical mixture material obtained approval levels by an average of 74.27% were classified as high. Keywords: Chemical Mixture, Learning Outcomes, Motivation, and Practicum